THE CONTRIBUTION OF A GENERAL TECHNICAL SUBJECT TO THE ISSUE OF THE CAREER CHOICE OF THE BASIC SCHOOL PUPILS - HAVELKA, Martin; KROPAC, Jiri (Trends in education, 2015)
The article deals the possibilities of support of the career choice during the realisation of the general technical subject's instruction. The educational sphere Clovek a svet prace (i.e. Man and the world of employment) contributes to the issue of the choice of further pupils' educational and professional path both directly (it allows the children to cognize the selected professions), and indirectly - by the development of the soft skills, including the self-efficacy and self-assessment. These are essential for the successful choice of the further educational path to be in accordance with the possibilities and abilities of the pupils.
Keywords: Educational sphere Clovek a svet prace; Man and the world of employment; technical education; career choice; career decision-making; factors of the career decision-making; selfconcept; self-image; obstacles in the process of the career choice.